The association between farmer characteristics, behavior, and pesticide spraying patterns and skin disorders in citrus farmers in Aji Mbelang Village, Karo Regency - Pane, Putri Yunita; Surbakti, Yemima Valentin Br; Saragih, Meysi Dea Vinata R.; Hartono; Simangungsong, Pahala Maringan Jubel (Buletin Kedokteran & Kesehatan Prima, 2025)
Agriculture forms a vital component of Indonesia’s economy, yet pesticide use poses significant occupational health hazards, particularly skin disorders from exposure. This study aimed to analyze the association between farmer characteristics, behavior, and pesticide spraying patterns with the incidence of skin disorders among citrus farmers in Aji Mbelang Village, Karo Regency. A quantitative analytical cross-sectional study was conducted involving 30 citrus farmers selected through accidental sampling. Data were collected using a structured questionnaire assessing demographic variables, behavioral factors, and pesticide spraying patterns. Univariate and bivariate analyses, including chi-square tests, were performed to explore associations between independent variables and skin disorder incidence, with significance set at p<0.05. The majority of respondents were male (86.7%), aged over 36 years (43.3%), and had completed senior high school (46.7%). The prevalence of skin disorders was high (90.0%). Most farmers demonstrated poor knowledge about pesticide risks (60.0%) but exhibited positive attitudes (86.7%) and safety practices (76.7%). Contradictorily, 96.7% engaged in high-risk spraying behaviors. Age was the only statistically significant variable associated with skin disorders (p=0.044), with all farmers over 32 years reporting skin disorders. Skin disorders are highly prevalent among citrus farmers and significantly associated with older age. The findings reveal a gap between positive safety attitudes and hazardous field practices, highlighting the need for targeted educational interventions to enhance knowledge and promote safer pesticide application to mitigate dermal health risks.